1996
DOI: 10.1093/carcin/17.11.2455
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of more malignant tumors by various genotoxic carcinogens in transgenic mice harboring a human prototype c-Ha-ras gene than in control non-transgenic mice

Abstract: In this study, we investigated the carcinogenic response of transgenic mice carrying the human prototype c-Ha-ras gene, namely Tg rasH2/CB6F1 mice, to various genotoxic carcinogens and compared it with that of control non-transgenic CB6F1 mice (non-Tg mice). The present studies were conducted as the first step in the evaluation of the Tg rasH2/CB6F1 mouse as a model for the rapid carcinogenicity testing system. Short-term (< or = 6 months) rapid carcinogenicity tests of various genotoxic carcinogens, 4-nitroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
117
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 14 publications
8
117
0
Order By: Relevance
“…The positive control for Tg rasH2 mouse studies has generally been a single intraperitoneal injection of N-methyl-Nnitrosourea (MNU) at a dose of 75 mg/kg (8,19,21). Single 37.5 or 75 mg/ kg injections of MNU appear to be appropriate treatment regimens for Tg rasH2 positive control groups (8).…”
Section: Introductionmentioning
confidence: 99%
“…The positive control for Tg rasH2 mouse studies has generally been a single intraperitoneal injection of N-methyl-Nnitrosourea (MNU) at a dose of 75 mg/kg (8,19,21). Single 37.5 or 75 mg/ kg injections of MNU appear to be appropriate treatment regimens for Tg rasH2 positive control groups (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that incidence of spontaneous tumors is generally low in rasH2-Tg mice during a 6-month study (20). Therefore, the rasH2-Tg mice model might be a useful tool for identi cation of genotoxic and/or nongenotoxic carcinogens for humans (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic animals harboring an oncogene and/or animals lacking a tumor suppressor gene are expected to be more susceptible to various carcinogens than normal animals [18]. Tg-rasH2 mice hemizygously carrying the prototype human c-Ha-ras gene, which were established by Saitoh et al [23], show high and rapid susceptibility to various carcinogens and are considered to be promising as an animal model for an alternative rapid carcinogenicity test [19,26]. In addition, the phenotypes of high and rapid carcinogenesis in transgenic mice may be useful for evaluating new anticancer drugs or cancer prevention.…”
Section: Introductionmentioning
confidence: 99%